CUT Fruit Sciences/Postharvest Group - (:unkn) unknown (My University, 2026)
We are part of the Department of Agricultural Sciences, Biotechnology and Food Science (ABF) at the Cyprus University of Technology (CUT), based in Lemesos, Cyprus. The Fruit Sciences/Postharvest Group was established by Dr. George Manganaris upon his recruitment at CUT in January 2009. Thanks to interdepartmental synergies, the Group managed to set up and routinely run an array of assays related to qualitative, physicochemical, phytochemical and biochemical properties of fresh produce. Our group has extensive research experience in issues related to postharvest physiology and technology of fresh produce, with special reference to fruit crops. Particular attention is given in the elucidation of fruit ripening at physiological, biochemical and molecular level with emphasis in the development of physiological disorders and their responsiveness to chilling temperatures. Additionally, CUT Fruit Sciences/Postharvest group is involved in synergies dealing with the application of preharvest treatments and novel technologies for maintaining quality of horticultural crops, including their responsiveness to abiotic conditions.